Women`s water polo world championships: Technical and tactical aspects of winning and losing teams in close and unbalanced games - Lupo, C.; Condello, G.; Capranica, L.; Tessitore, A. (The Journal of Strength and Conditioning Research, 2014)
This study aimed to compare the technical and tactical aspects between winning and losing teams in close (i.e., 1-3 goals of difference) and unbalanced (i.e., >3 goals of difference) elite women`s water polo games. A notational analysis was performed on 45 games to evaluate occurrence of action, mean duration, action outcome, origin and execution of shot, offensive and defensive role, and arrangement of even, counterattack, power play, and transition situations. Independent 2-sided t-tests were applied to show differences (p < 0.05) between teams. Regarding close games, effects emerged for action outcome (counterattack: lost possessions; power play: goals, no goal shots), origin (even: zone 1, zone 4; counterattack: zone 1, zone 5) and execution (even: off-the-water shots; counterattack: shots after > than 2 fakes; power play: drive shots) of shots, offensive even arrangements (6 vs. 6/5 vs. 5; 2 vs. 2/1 vs. 1), and role. Regarding unbalanced games, differences emerged for the occurrence of action (even, counterattack), duration (even; power play), action outcome (even: goals, penalties; counterattack: goals, no goal shots, penalties; power play: goals, no goal shots; transition: lost possessions), origin (even: zone 2, zone 4; counterattack: zone 5) and execution (even: free throws, drive shots; counterattack: drive shots, shots after > 2 fakes; power play: drive shots, shots after 1 fake) of shots; offensive even arrangements (2 vs. 2/1 vs. 1), and role; and defensive even arrangements (pressing, zones 1-2, zone M, zones 2-3-4). Differences between close and unbalanced games underlining that water polo performance should be analyzed in relation to specific margins of victory. Therefore, water polo coaches and physical trainers can plan a sound training session according to the most important aspects of close (opponent`s exclusion, center forward play, and power play actions) and unbalanced (defensive skills) games.